Mifepristone-misoprostol combination treatment for early pregnancy loss after embryo transfer: a case series - Leah Esposito; Molly Siegel Kornfield, M.D; Elizabeth Rubin, M.D; Thomas O'Leary, Ph.D; Paula Amato, M.D; David Lee, M.D; Diana Wu, M.D; Sacha Krieg, M.D., Ph.D; Pamela B. Parker, M.D., M.P.H (Elsevier, 2023)
Objective: Evidence strongly supports the use of mifepristone-misoprostol combination treatment for early pregnancy loss (EPL) among pregnancies conceived without assisted reproductive technologies. No literature exists, however, regarding the efficacy of this treatment in the medical management of EPL among pregnancies after in vitro fertilization and embryo transfer (IVF-ET). These patients differ as some use exogenous hormonal supplementation to provide pregnancy support. Thus, the management for EPL may differ between unassisted conceptions and those after ET. Mifepristone, a progesterone receptor antagonist, may demonstrate an altered treatment effect when used with misoprostol to manage EPL in assisted reproductive technologie-conceived pregnancies. Objective: To describe our institution's experience using mifepristone-misoprostol to manage EPL after in vitro fertilization with embryo transfer IVF-ET. Design: Retrospective case series Setting: Single academic institution from 2020 to 2022. Patients(s): Nine patients with ultrasound confirmed EPL after IVF-ET. Intervention(s): All 9 patients underwent in vitro fertilization followed by fresh or frozen embryo transfer. All 9 received 200 mg of mifepristone 24 hours before 800 μg of misoprostol. Main Outcome Measurement(s): Incomplete abortion, need for surgical management, number of days to negative serum human chorionic gonadotropin (hCG). Result(s): Of the 9 subjects included, one had a programmed frozen embryo transfer cycle, 6 had modified natural frozen embryo transfer cycles, and 2 underwent fresh ET. Eight subjects had successful expulsion of tissue with one dose of treatment, and one required uterine aspiration. No subjects required additional dosing of misoprostol. The mean number of days elapsed from mifepristone treatment to tissue expulsion was 4.89 ± 11.30 days and the mean days to negative-range serum hCG was 36.89 ± 18.59 days. At the initial ultrasound, all pregnancies had one gestational sac seen; 5/9 had a yolk sac; only 3 had fetal cardiac activity. The mean gestational age at the time of EPL diagnosis was 55.22 ± 8.77 days, with the majority (8/9) having completed 7 weeks gestation. Conclusion(s): Mifepristone-misoprostol combination treatment appears to be a reasonable option for those with EPL after IVF-ET. Future, larger-scale studies are needed comparing combination treatment with misoprostol only among various ET protocols.